Pengaruh Earnings Per Share (EPS), Loan To Deposit Ratio (LDR), dan Arus Kas Operasi terhadap Harga Saham Emiten Sektor Perbankan di Bursa Efek Indonesia - Alvin Setiawan; Lauw Tjun Tjun (Jurnal Akuntansi, 2010)
When investors do the investing, they have to receive some sufficient information to make investing decision, therefore investors look for the financial statements issued by the emiten and do the fundamental and technical analytic. The writer focused on banking company that listed in BEI (Bursa Efek Indonesia) at periode 2007-2009. The writer took variable Earnings Per Share as profit indicator, variable Loan to Deposit Ratio as liquidity indicator and Cash Flow from Operating Activity as company’s performance indicator. The objective in this study is to determine the influence of Earnings Per Share , Loan to Deposit Ratio and Cash Flow from Operating Activity on Stock Price both it partially or simultaneusly. This study used hypotesis test and the data processed by Statistical Package for the Social Sciences (SPSS) program with regression test. The result of this study partially shows that Earnings Per Share and Loan to Deposit Ratio have significant influence to Stock Price, meanwhile Cash Flow from Operating Activity has no significant effect to Stock Price. Simultaneusly, Earnings Per Share , Loan to Deposit Ratio and Cash Flow from Operating Activity have significant influence to Stock Price. Keywords : Earnings Per Share , Loan to Deposit Ratio, Cash Flow from Operating Activity and Stock Price